Hemeroteca literaria española, 1924-1931 - Osuna, Rafael (Iluminaciones, 2007)
Author's research on four journals of the Generación del 27: Parábola (1927-1928), Manatial (1928-1929), Meseta (1928-1929), and La Rosa de los Vientos.